Social media and pornography access behavior among adolescents - Niken Meilani; Sunarru Samsi Hariadi; Fransiskus Trisakti Haryadi (International Journal of Public Health Science (IJPHS), 2023)
Adolescents were vulnerable to problems related to reproductive health. Generation Z was the largest proportion in Indonesia who was born with internet and technology literacy. Internet and social media were meaningful for them. In 2018, 57% of adolescents worldwide search out porn using the internet. This study’s goal was to analyze pornography access among males and female’s adolescent. This was a quantitative study with a cross-sectional approach. The study population was high school students in Yogyakarta. A multistage random sampling was employed, involving 80 respondents. The data were analyzed using the Chi-square test, and logistic regression. The results showed that all the respondents had smartphones and accessed media social. WhatsApp, Instagram, and YouTube were the most accessed. Most of them (57.5%) had access to pornography through films, short videos, and also pictures. Multivariate analysis showed that male adolescents (Exp B=13.7) had a greater risk of accessing pornography compared to females. Access to more than 4 types of social media also increases access to pornography (Exp B=6.8). Adolescence needs more information, and also guidance from family, school also community related to their use of smartphones and social media to prevent access to pornography as the opening gate for sexual risk behavior.